Free volume correlation with ac conductivity and thermo-mechanical properties of poly (ethylene oxide)-silica nanocomposites. (August 2019) - Utpalla, P.; Sharma, S.K.; Sudarshan, K.; Kumar, V.; Pujari, P.K.
Graphical abstract: AC conductivity ( σ, Scm −1 ) of PEO-silica nanocomposites vs. relative free volume ( f v, %) follows logσ = a + bexp (fv /c), where a, b, c are the fitting parameters. Highlights: PEO-silica nanoparticles composite films up to loading 20 wt% have been prepared. Silica nanoparticles impose physical confinement to PEO chains in the composites. The ductility of the films increases with loading up to 10 wt%. The ac conductivity of the films increases linearly with silica loading. AC conductivity of the films increases drastically after a critical free volume fraction. Abstract: Poly(ethylene oxide), PEO, based nanocomposites are shown to have higher ionic conductivity compared to pure PEO. In order to investigate the exclusive role of free volume structure of amorphous region of PEO on its electrical conductivity, PEO-silica nanoparticles composite films have been prepared with different silica loadings. The free volume fraction of polymer composites measured using positron annihilation lifetime spectroscopy (PALS) was observed to increase nonlinearly with the increase in loading of silica. The increase in free volume on silica loading has been attributed to PEO-silica interphase as well as newly created amorphous PEO. At higher loading, positron annihilation from regions near silica particles has been confirmed by coincidence Doppler broadening measurements. Thermal analysis of polymer nanocomposites shows a decrease in crystallinity and crystallite melting temperature with the increase in silica loading. The PEO-silica nanocomposite films showed enhanced ac conductivity as well as mechanical properties (higher Young's modulus and ductility). The observed changes in free volume structure and semicrystalline morphology of PEO matrix are attributed to the physical confinement imposed by presence of silica nanoparticles in PEO matrix. The present study shows that free volume measured using PALS has a direct relation with ac conductivity which is observed to increase drastically after a critical free volume fraction.